A new occurrence of ambient inclusion trails from the 1900‐million‐year‐old Gunflint Formation, Ontario: nanocharacterization and testing of potential formation mechanisms. Issue 5 (17th May 2016) - Wacey, D.; Saunders, M.; Kong, C.; Kilburn, M. R.
Abstract: Ambient inclusion trails (AITs) are tubular microstructures thought to form when a microscopic mineral crystal is propelled through a fine‐grained rock matrix. Here, we report a new occurrence of AITs from a fossilized microbial mat within the 1878‐Ma Gunflint Formation, at Current River, Ontario. The AITs are 1–15 μm in diameter, have pyrite as the propelled crystal, are infilled with chlorite and have been propelled through a microquartz (chert) or chlorite matrix. AITs most commonly originate at the boundary between pyrite‐ and chlorite‐rich laminae and chert‐filled fenestrae, with pyrite crystals propelled into the fenestrae. A subset of AITs originate within the fenestrae, rooted either within the chert or within patches of chlorite. Sulphur isotope data ( 34 S/ 32 S) obtained in situ from AIT pyrite have a δ 34 S of −8.5 to +8.0 ‰, indicating a maximum of 30 ‰ fractionation from Palaeoproterozoic seawater sulphate (δ 34 S ≈ +20 ‰). Organic carbon is common both at the outer margins of the fenestrae and in patches of chlorite where most AITs originate, and can be found in smaller quantities further along some AITs towards the terminal pyrite grain. We infer that pyrite crystals now found within the AITs formed via the action of heterotrophic sulphate‐reducing bacteria during early diagenesis within the microbial mat, as pore waters were becoming depleted in seawater sulphate. Gases derived from this process such as CO2 and H2 S were partially trapped within the microbial mat, helping produce birds‐eye fenestrae, while rapid microquartz precipitation closed porosity. We propose that propulsion of the pyrite crystals to form AITs was driven by two complementary mechanisms during burial and low‐grade metamorphism: firstly, thermal decomposition of residual organic material providing CO2, and potentially CH4, as propulsive gases, plus organic acids to locally dissolve the microquartz matrix; and secondly, reactions involving clay minerals that potentially led to enhanced quartz solubility, plus increases in fluid and/or gas pressure during chlorite formation, with chlorite then infilling the AITs. This latter mechanism is novel and represents a possible way to generate AITs in environments lacking organic material.